'Wasn't This Already Considered Sexual Harassment?': Exploring the Confusion Around the Law Mandating Consent to Receive a Nude Sext Message. Issue 3 (3rd July 2022) - Evans, Amelia E.; Currin, Joseph M.; Garos, Sheila; Stokes, Alyssa; Cox, Kassidy; Meyer, Cody L.
Abstract: With the majority of individuals in the United States owning a mobile device, communicating via text is popular. Many individuals who text also engage in sexting, commonly defined as sending a sexually suggestive or explicit message that can include a nude image. In September of 2019, Texas passed a law prohibiting the sending of an unsolicited nude image without consent from the receiver. The goal of the study was to capture the reactions of individuals to this state law. There were 400 different responses by 400 different individuals posted on Reddit by users expressing their reactions to the passing of the state law. Initial reactions were captured, chosen from specific Reddit threads containing the link to the law within 1 month of the law being passed. These comments were collected and the research team used thematic analysis to highlight the themes to users' responses to the sexting law. Of note was the sizeable number of individuals who disapproved of the law, highlighting a lack of knowledge about consent to engage in sexual behaviors in general, the need to gain consent to engage in sexting, and a misunderstanding of what defines sexual harassment. Implications for sex education programs and policy makers are discussed.